An assessment of the effectiveness of peace clubs as a peace building strategy: the case of Matobo (ward 10): 2008 - 2013 - Ngwenya, Nokukhanya (Midlands State University, 2018)
This study is a qualitative research conducted in Matobo ward 10. It aims to explore if peace clubs are an effective strategy for Peace Building. Violence is prevalent in many communities leaving traumatic experiences which have perpetuated hatred and dysfunctional communities. Information obtained through interviews and questionnaires is the basis of the narration of the findings of this research. The results of the study revealed that although peace clubs are relevant in Peace Building peace has remained an elusive goal. The area understudy is politically polarized, economically crippled with high unemployment and drought prevalent which makes it a food relief case. Peace clubs also fail because the NGO which facilitate them imposed them to the community hence they are not inclusive as they only encompass youths. The researcher therefore recommends Peace Building strategies like peace clubs to be inclusive and have a grassroots approach so as to establish the needs of the people as far as peace is concerned.